Educação física escolar e autonomia: a prática pedagógica sob a perspectiva freireana - Oliveira, Glaurea Nádia Borges de (2011)
Grounded in the principles of Freire s perspective, this research aimed to identify, in the context of Physical Education, the elements that could be understood as characteristics of a pedagogical practice that encourages the autonomy process construction of students. To do so, it was performed a case study on the work of a Physical Education teacher of a public school and her class of students from 3rd grade. Her selection as a participant was based on prior clues that her pedagogical practice promoted students autonomy and, based on this initial hypothesis, this study sought to understand the characteristics and specificities of this practice. The information needed to elucidate the research problem were produced by the following procedures: class observations, semi-structured interview, reflexive meeting and documents analysis. The obtained data revealed two structuring categories of pedagogical practice focused on: 1) questioning and dialog and 2) the exercise of democratic teacher authority. The first category is divided into three subcategories: a) appreciation of students' knowledge, b) participatory and stimulating experiences of decision and c) social, cultural, political, economic and ideological implication of content, each one consisting of specific elements. The second category does not include subdivisions and it was directly analyzed from its constituent elements. It was also constructed a third explanatory category a critical reflection of the own practice that allowed a better understanding of the issues identified in the two previous categories. The results confirmed the initial hypothesis and showed that a pedagogical practice viewed as favoring the students autonomy, besides having essentially a democratic characteristic, manifests itself from a constant readiness for change. This readiness is underpinned by the established relationships between to do and thinking about to do and by critical recognition of factors that constrain and limit the educational work. It was possible to conclude that all these characteristics were features of an autonomous teacher and therefore, the possibility of development of students' autonomy is rooted in the teachers autonomy, which reiterates the need to question the current conditions of teaching formation and practice